The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/2013gl058785
|View full text |Cite
|
Sign up to set email alerts
|

Air‐water gas exchange and CO2 flux in a mangrove‐dominated estuary

Abstract: [1] Mangrove forests are highly productive ecosystems, but the fate of mangrove-derived carbon remains uncertain. Part of that uncertainty stems from the fact that gas transfer velocities in mangrove-surrounded waters are not well determined, leading to uncertainty in air-water CO 2 fluxes. Two SF 6 tracer release experiments were conducted to determine gas transfer velocities (k(600) = 8.3 ± 0.4 and 8.1 ± 0.6 cm h À1 ), along with simultaneous measurements of pCO 2 to determine the air-water CO 2 fluxes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…As shown by Ho et al (2014), pCO 2 observed during SharkTREx 1 and 2 fall in the upper range of those reported in other estuarine (Borges, 2005) and mangrove-dominated systems (Bouillon et al, 2003(Bouillon et al, , 2007aKoné and Borges, 2008;Call et al, 2015). The mean air-water CO 2 fluxes in Shark River for SharkTREx 1 and 2 were 105 ± 9 and 99 ± 6 mmol m −2 d −1 (Ho et al, 2016).…”
Section: Air-water Co 2 Fluxesmentioning
confidence: 55%
See 4 more Smart Citations
“…As shown by Ho et al (2014), pCO 2 observed during SharkTREx 1 and 2 fall in the upper range of those reported in other estuarine (Borges, 2005) and mangrove-dominated systems (Bouillon et al, 2003(Bouillon et al, , 2007aKoné and Borges, 2008;Call et al, 2015). The mean air-water CO 2 fluxes in Shark River for SharkTREx 1 and 2 were 105 ± 9 and 99 ± 6 mmol m −2 d −1 (Ho et al, 2016).…”
Section: Air-water Co 2 Fluxesmentioning
confidence: 55%
“…1). The mean depths of Tarpon Bay, Shark River, and Harney River at mid-tide are 1.4 ± 0.3, 2.8 ± 0.4, and 2.6 ± 0.4 m (Ho et al, 2014), respectively, and the surface areas are 1.48 × 10 6 , 2.54 × 10 6 , and 2.75 × 10 6 m 2 , respectively. The inter-tidal zones bordering the Shark and Harney rivers are dominated by Rhizophora mangle (red mangrove), Avicennia germinans (black mangrove), Laguncularia racemose (white mangrove), and Conocarpus erectus (buttonwood).…”
Section: Study Sitementioning
confidence: 98%
See 3 more Smart Citations